Window Shopping Model Based on Smart Crossword Puzzle: A Creative Strategy in Learning to Determine Content and Write Pantun - Sri Listiana Izar; M. Afiv Toni Suhendra Saragih; Yayuk Hayulina Manurung (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study aims to develop and validate the Window Shopping Learning Model assisted by the Smart Crossword Puzzle Application to improve students' pantun writing skills. The research method used is Research and Development (R&D) by applying the ADDIE (Analysis, Design, Development, Implementation, Evaluation) instructional design model. Data were collected through needs questionnaires, validation sheets, trials, and Focus Group Discussions (FGDs), then analyzed using descriptive statistics and the Kendall's W conformity test.The design phase produced a preliminary model with student worksheets, poem guidebooks, visual cues, and assessment indicators. Expert validation showed the model was feasible (average score 3.9), with high agreement among experts (Kendall’s W: ?²_calculated = 19.571 > ?²_table = 14.107). Revisions improved language, evaluation alignment, and visuals. Small group trials indicated the model was practical and effective, with usability scores averaging 4.18. FGD evaluations confirmed high effectiveness and acceptance, with scores of 4.79–4.84. In conclusion, the model is valid, practical, and effective, providing an innovative and culturally relevant method for teaching pantun in higher education.